Favoriser l'engagement moteur des élèves en éducation sportive et physique : les effets des usages du temps mesurés en première et en troisième personne - Oriane Petiot; Jacques Saury (Nantes Université, 2021)
This study aimed to analyze the effects of the teacher's "use of time" (Chopin, 2010) on the student motor engagement in PE. First, we adopted a "first person" approach, filming an expert EPS teacher during the first PE unit of the year (seven volley-ball lessons) in front of high school students, then we realized with him a self-confrontation interview after each lesson. Second, we tested the teacher's point of view by adopting a "third person" approach, consisting of measuring the quantitative and qualitative engagement of students from an observable point of view. The "first person" approach revealed four categories of use of time by the teacher. The main were: "Pressing students to limit wasted time" and "Boosting student engagement in volleyball". The teacher sometimes perceived positive effects of his use of on the students motor engagement, and sometimes a lack of effects, especially when their engagement wasn't dynamic. According to the "third person" approach, the students motor engagement time increased significantly over the lessons. However, these positive effects of the teacher's use of time were erratic and variable. There were convergences and divergences between the effects perceived by the teacher and the observed effects. These results are discussed in terms of their theoretical interests and their contributions to teaching.